Bacterial colonisation and localisation in ovine interdigital dermatitis and footrot - Agbaje, M (2018)
Ovine footrot is the major cause of lameness in sheep within the UK and an economic and welfare concern for sheep farmers globally. It is characterised by under-running of the hoof-horn and preceded by interdigital dermatitis (ID). Under-running footrot is attributed to the host immune response, which is provoked primarily by Dichelobacter nodosus in addition to other bacteria pathogens. However, the precise role of these other bacteria is yet unknown. Therefore, we hypothesise that bacterial invasion and colonisation of the ovine interdigital skin contributes to a strong host inflammatory response leading to the characteristic histopathology observed. In this context, this study examined host inflammatory response [inflammatory cell infiltration, pro-inflammatory cytokines (IL-1β)], histopathological lesions and virulent D. nodosus abundance in healthy, ID and footrot conditions in an attempt to gain further insights into the pathogenesis of this important disease. To investigate this hypothesis, two studies were designed: (i) to grade histological lesions in different clinical conditions and (ii) to determine bacterial localisation in post-slaughtered interdigital skin biopsies from the abattoir. Standardised histology lesion grading systems were developed and applied using histochemical techniques (haematoxylin and eosin (H&E), periodic acid Schiff PAS). Bacterial localisation was determined in serial horizontal sections across skin depths combining histology (transverse cryosections + H&E) and qPCR technique for the quantification of bacterial DNA. Furthermore, parallel data of IL-1β expression and virulent D. nodosus load obtained from a different study were compared to histology lesions. Key findings were as follows: (i) histological lesions (cell ballooning, parakeratosis, epidermal micro-abscesses and inflammatory cell infiltration) were similar in all clinical conditions, (ii) increased inflammatory cell infiltration score corresponded significantly with high levels of IL-1β expression (p<0.05) in footrot, and virulent D. nodosus load (p<0.001) across all clinical conditions, (iii) across different skin depths, eubacteria localisation was consistent, D. nodosus localisation was highly variable while F. necrophorum was localised in deeper sections of healthy feet. In addition, eubacteria load was significantly higher (p=0.0002) in the epidermis near the skin surface (≤200µm) of footrot disease samples when compared to healthy samples. Eubacteria components may play contributory roles in footrot pathogenesis based on their localisation in interdigital skin. In conclusion, contrary to previous notion that the severity of disease condition was dictated by progressive pathology, data in this study showed no appreciable difference in the levels of histological lesions and inflammatory response between healthy and diseased (ID, footrot) conditions. Histological lesions and the bacterial components of the skin including the virulent D. nodosus contribute to the local inflammatory response which probably drives the progression of footrot disease.